The Use of Group-Work, Reward-Punishment, and Visual Media as an Integrated Teaching-Learning Strategy to Improve the EL T Classroom Interaction of the 8th Grade Students of MTs NW Hikmaturrahim, Lombok Tengah - Azis, Yek Amin; Tou, Asruddin Barori (JOURNAL OF EDUCATION, 2014)
This research aimed at observing and describing the processes and the results of the actions implemented in improving the ELT classroom interaction of the gh grade students of MTs NW Hikmaturrahim, Lombok Tengah. This research was a collaborative action research study. The subjects were the English teacher and the gh grade students of MTs NW Hikmaturrahim, Lombok Tengah in the academic year of 201112012. There were two steps in conducting this research, namely reconnaissance and action. The research instruments used in this study were observation sheets and questionnaire. The data were collected through observation and questionnaire. The results of the research are as follows. After implementing the group-work, reward-punishment, and visual media as an integrated teaching-learningstrategy in two cycles, the students were not afraid in speaking, all groups felt brave to speak with the English teacher or with other students, almost all of the students were active in the classroom interaction with the English teacher or with other students, the students were more motivated to study than before, it could overcome the students' laziness to study, and, the students were interestedin the ELT process.